FIGURATIVE LANGUAGE IN WILLIAM SHAKESPEARE AND WILLIAM WORDWORTH’S POEM - Vivi Melaty Ruslida; Barnabas Sembiring; Indah Damayanti (Edu-Ling: Journal of English Education and Linguistics, 2019)
This study aims to determine the use and meaning of figurative language (majas) in poetry. The sample of this study is ten poems from two different writers of the era, namely Shakespeare and Wordsworth. This research uses a descriptive qualitative method and an objective approach used to analyze data. Figurative language (majas) was analyzed based on theories from Wren and Martin and also analyzed the meaning of each figurative language (majas) that had been discovered. The figurative language (majas) found is presented in tabular form. From the data analysis, all figurative languages ??(majas) were found in Shakespeare's five poems except Euphemism and Irony. In Wordsworth's poem, all figurative languages ??(majas) are found except Synecdoche and Irony. From the figurative language (majas) that has been found and from the author's background, it has been concluded that Shakespeare is a Poetic person, he usually uses some beautiful words. Meanwhile, Wordsworth is a Romantic person. He usually talks about love, feelings and even sadness which is always associated with the loss of someone he loves.